Introduction to Basic Legal Citation - Martin, Peter W. (Open textbook library., 2013)
This is not a comprehensive citation reference work. Its limited aim is to serve as a tutorial onhow to cite the most widely referenced types of U.S. legal material, taking account of localnorms and the changes in citation practice forced by the shift from print to electronic sources.It begins with an introductory unit. That is followed immediately by one on "how to cite" thecategories of authority that comprise a majority of the citations in briefs and legalmemoranda. Using the full table of contents one can proceed through this material insequence. The third unit, organized around illustrative examples, is intended to be used eitherfor review and reinforcement of the prior "how to" sections or as an alternative approach tothem. One can start with it since the illustrative examples for each document type are linkedback to the relevant "how to" principles. The sections on abbreviations and omissions, on typeface (italics and underlining), and onhow citations fit into the larger project of legal writing that follow all support the precedingunits. They are accessible independently and also, where appriopriate, via links from theearlier sections. Finally, there are a series of cross reference tables tying this introduction tothe two major legal citation reference works and to state-specific citation rules and practices. The work is also designed to be used by those confronting a specific citation issue. For suchpurposes the table of contents provides one path to the relevant material. Another, to whichthe bar at the top of each major section provides ready access, is a topical index. This index isalphabetically arrayed and more detailed than the table of contents. Finally, the searchfunction in your e-book reader software should allow an even narrower inquiry, such as oneseeking the abbreviation for a specific word (e.g.,institute) or illustrative citations for aparticular state, Ohio, say. If the device on which you are reading this e-book allows it, the pdf format will enable you toprint or to copy and paste portions, large or small, into other documents. However, since thev work is filled with linked cross references and both the table of contents and index rely onthem, most will find a print copy far less useful than the electronic original.